Presenting Hayek’s Theory of Social Justice in the Context of His Intellectual Journey and Some Critiques on It - Vahid Moghadam; Marjan Esmaili Karbasi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Social justice is one of the most widely used concepts in the social sciences and at the same time one of the most challenging. One end of the spectrum of theorizing is for the deniers and the other for the egalitarians. Although Von Hayek is considered as one of the steadfast deniers of justice, this view is not very accurate. The study of the cycles of intellectual life and the understanding of the theory of justice in the context of these cycles makes it clear that he should be considered as an institutionalist who emphasizes the importance of very abstract rules in governing free societies to solve the problem of harmony in economics. Distributive justice conflicts with such rules and leads to the creation of wealthy tribal communities because it causes inefficiency by failing to harmonize the economy. This method of theorizing has been neglected in many theories of justice, even in the most famous ones, because they do not pay much attention to the way people interact in society. At the same time, there are criticisms of this theory, including its lack of attention to the formation of interest groups in the economy, market failures, difficulty in recognizing fair rules of the game, and lack of attention to the negative impact of large inequalities on social order.